Combination of obstructive sleep apnoea and insomnia treated by continuous positive airway pressure with the SensAwake pressure relief technology to assist sleep: a randomised cross-over trial protocol. Issue 10 (27th October 2017) - Pepin, Jean Louis; Gagnadoux, Frédéric; Foote, Alison; Vicars, Rachel; Ogra, Bhavi; Viot-Blanc, Véronique; Benmerad, Meriem; D'Ortho, Marie-Pia; Tamisier, Renaud
Abstract : Introduction: Obstructive sleep apnoea (OSA) is a common sleep breathing disorder affecting up to 17% of the middle-aged population. Continuous positive airway pressure (CPAP) is the primary treatment for patients with OSA, but acceptance and adherence to therapy is suboptimal in specific subgroups particularly those with insomnia or poor sleep quality (40%–80% of patients with OSA). Pressure intolerance, particularly during periods of wakefulness, inhibiting sleep onset or return to sleep, is one reason for poor CPAP adherence. AutoCPAPs continually monitor airflow changes and only increase the pressure when the upper airway requires it. Reducing the pressure during wakefulness-sleep transition and wakefulness-after-sleep-onset (WASO) may improve therapy comfort and potentially adherence without compromising therapy efficacy. We hypothesise that SensAwake, a pressure relief function that reduces CPAP pressure on the transition from sleep to wakefulness and on WASO, may improve objective sleep quality. Methods and analysis: This is a multicentre, randomised double-blind crossover clinical trial on patients with both OSA and insomnia. Insomnia is defined as Insomnia Severity Index >15 at screening. Baseline data, including actigraphy, are collected for 1 week before randomisation (1:1) to either conventional AutoCPAP or AutoCPAP with SensAwake for 4 weeks. After an evaluation visit, patients are switched to the other treatment arm for a further 4 weeks. Allowing for 20% dropout, 48 patients are required. If applicable, repeated measures analysis of variance will be used to assess differences in WASO measured by actigraphy (primary outcome), other actigraphy measures, AutoCPAP compliance, subjective questionnaire scores (Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, Short-Form 12 Health Survey) and 24 hours blood pressure (secondary outcomes). Ethics and dissemination: The protocol was approved by the regional Ethics Committee (CPP Sud-Est–V, IRB N°6705) on 9 December 2015, is registered on ClincalTrials.gov (NCT02721329 ) and started in June 2016 with expected publication of primary outcome results in 2018. Trial registration number: NCT0272132 ; Pre-results.